SCHOOL MANAGEMENT AND EVALUATION: THE CHALLENGES OF THE SCHOOL MANAGER NOWADAYS - Oliveira, Marcos Diego de; Santos Cruz, Jose Anderson [UNESP] (Unesp-faculdade Ciencias & Letras, 2022)
The aim of the study is to present the main challenges that school managers encounter in their professional trajectory. Research on the topic of Institutional Management and Evaluation has increased and has focused on the analysis of the leader as a person and on leadership roles and tasks. The justification and relevance for this study lies in the influencing action that school management has historically had related to the role and functions of its staff in the educational unit it operates. What are the structures and strategies for training and qualifying managers so that they can overcome the constant challenges in management using institutional evaluation as a tool for better effectiveness in school management? The article is a systematic review. This study sought to demonstrate that the leadership exercised by managers is fundamental and can have a positive impact on the learning outcomes of students, given the challenges encountered in the management
Keywords: Management; Evaluation; Leadership; School